Effortful Control of University Students (Journal Of Educational and Psychological Researches, 2025)
The current research aims to identify the effortful control of university students. The research sample consists of 220 male and 334 female students, who were selected randomly from the University of Baghdad for the morning study. To achieve the objectives of the research, the researcher adopted the effortful control scale developed by Rothbart & Evans (2007), which consists of 16 items; it was translated and presented to a specialized jury of educational and psychological sciences. The researcher used the one-sample test, two independent samples test, Pearson correlation coefficient, alpha equation Kurtenbach (confirmatory factorial analysis), and hyperbolic regression analysis of the Pearson correlation coefficient to analyze data. The results showed that the research sample has Effortful control. In light of the results, the researcher recommended conducting courses and seminars that promote and raise awareness among students about the concept of effortful control, how to manage and control impulses and temptations, and encourage planning and setting long-term goals. Organizing awareness exhibitions and publications about effortful control and its main components that contribute to its effectiveness in self-regulation and its importance in professional life, education, relationships, and personal growth. Encouraging faculty members to hold courses and training programs, such as cognitive training to enhance executive functions, including working memory and inhibitory control, and self-training programs that help with regular self-reflection so that students become more aware of their thoughts, emotions, and behaviors, facilitating self-regulation. Moreover, he suggested conducting studies on "stressful control" with another sample, such as faculty members. Link the variable "stressful control" with other variables such as "mind wandering and mobile phone addiction." Conduct a study to explore the relationship between stressful control and academic achievement and how these factors influence each other and identify effective interventions